2014
DOI: 10.1371/journal.pone.0110305
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Tumor Size of Small Lung Adenocarcinomas Evaluated with Mediastinal Window Settings on Computed Tomography

Abstract: BackgroundWe aimed to clarify that the size of the lung adenocarcinoma evaluated using mediastinal window on computed tomography is an important and useful modality for predicting invasiveness, lymph node metastasis and prognosis in small adenocarcinoma.MethodsWe evaluated 176 patients with small lung adenocarcinomas (diameter, 1–3 cm) who underwent standard surgical resection. Tumours were examined using computed tomography with thin section conditions (1.25 mm thick on high-resolution computed tomography) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Several studies of PADC have reported that lesions eliminating ground glass opacity on HRCT images and those excluding lepidic growth lesions on pathology examination correlated with prognosis after resection [4][5][6][7][8][9][10][11][12]16,17]. However, there are only a few studies on the use of HRCT images to preoperatively estimate the newly proposed pathological invasive size of PADC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of PADC have reported that lesions eliminating ground glass opacity on HRCT images and those excluding lepidic growth lesions on pathology examination correlated with prognosis after resection [4][5][6][7][8][9][10][11][12]16,17]. However, there are only a few studies on the use of HRCT images to preoperatively estimate the newly proposed pathological invasive size of PADC.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that the degree of invasion and the prognosis after resection are correlated with the tumor disappearance ratio on chest HRCT, that is, the ratio of tumor dimension in the mediastinal window setting to the whole tumor dimension in the lung window setting [4][5][6]. Other studies suggested that the degree of invasion and the prognosis after resection are correlated with the solid part of the tumor in the lung window setting [7][8][9][10] or with absolute values of the whole-tumor dimension in the mediastinal window setting [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This method has been called the tumor disappearance rate or ratio. 24,[98][99][100] This is important because it has been shown that measuring the solid component of subsolid nodules correlates best with the likelihood of tumor invasion. Furthermore, use of narrow (mediastinal) windows facilitates demonstration of both the increasing overall tumor density and the increasing size of any solid components over time.…”
Section: Display Window Settingsmentioning
confidence: 99%
“…Approximately 25% of cases detected at an early‐stage are candidates for surgical resection . Tumor size and nodal metastasis are well‐known prognostic factors in resected early‐stage lung ADC and one of the major factors that is considered in the treatment strategy. Additionally, given the advancing age of many patients diagnosed with lung ADC, there is a more prevalent risk for significant comorbidities in the aged population .…”
Section: Introductionmentioning
confidence: 99%